2011
DOI: 10.1149/2.003111jes
|View full text |Cite
|
Sign up to set email alerts
|

GaN-Based LEDs Grown on HVPE Growth High Crystalline Quality Thick GaN Template

Abstract: In this study, high crystalline quality 30 μm thick gallium nitride (GaN) films were grown by hydride vapor phase epitaxy (HVPE) on sapphire substrate, and the thick GaN films were used for developing high performance light-emitting diodes (LEDs). By using high-resolution X-ray diffraction, the full width at half-maximum (FWHM) of the rocking curve shows that this 30 μm thick GaN template had high crystalline quality. In addition, the transmission electron microscopy (TEM) images suggest that threading disloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Compared with LED-R, LED-1, and LED-2 had 47.8% and 20.1% higher output power, respectively. Such great enhancement in light output power results from the improved crystal quality and released strain of the films [11]. Therefore, the EL emission peak wavelength, Raman spectrum, and relative internal quantum efficiency (IQE) were measured to support the conclusion mentioned above.…”
Section: Methodsmentioning
confidence: 72%
See 3 more Smart Citations
“…Compared with LED-R, LED-1, and LED-2 had 47.8% and 20.1% higher output power, respectively. Such great enhancement in light output power results from the improved crystal quality and released strain of the films [11]. Therefore, the EL emission peak wavelength, Raman spectrum, and relative internal quantum efficiency (IQE) were measured to support the conclusion mentioned above.…”
Section: Methodsmentioning
confidence: 72%
“…The Raman spectra of the samples grown through step-1 and step-2 uGaN growth were measured. The Raman shifts of the (Table I), while the unstrained GaN epitaxial layer was located at 566.5 cm −1 [11]. The Raman shift of the E 2 high mode for sample-1 and sample-2 shifted to a low frequency because of the thick GaN films grown through HVPE.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been reported that the improvement of the crystalline quality can effectively enhance the internal quantum efficiency (IQE) of the InGaN/GaN multiple quantum wells (MQWs) [32]. In order to clarify the correlation between the crystalline quality and IQE for LED grown on planar sapphire substrate, CPSS and cone-shaped SiO patterned template, the photoluminescence (PL) internal quantum efficiency (IQE) measurement was performed.…”
Section: Resultsmentioning
confidence: 99%